2015
DOI: 10.1016/j.ijrobp.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Tumor Response of Non-Small Cell Lung Cancer Patients With 18F-Fludeoxyglucose Positron Emission Tomography: Potential for Treatment Individualization

Abstract: Evaluation of the early response in NSCLC patients showed that it is feasible to determine a threshold value for effective radiosensitivity corresponding to good response. It also showed that a threshold value for the fraction of negative αeff could also be correlated with poor response. The proposed method, therefore, has potential to identify candidates for more aggressive strategies to increase the rate of local control and also avoid exposing to unnecessary aggressive therapies the majority of patients res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…Although the atlas has an impact on a significant number of patients, its applicability is limited to 40% to 50% of the patients receiving chemotherapy and radiation therapy by excluding patients whose tumor grows or shrinks very little. Studies using clinical data and radiomics (1719) have demonstrated that quantitative image features extracted from pretreatment scans can be used to predict tumor response (eg, volume shrinkage) to chemotherapy and radiation therapy, thereby identifying patients who may not benefit from PTP in advance of radiation therapy. However, even if the stratification of patients to PTP is wrong, the simultaneous integrated boost to the target predicted by PTP becomes a randomly located hot spot within the initial PTV, which would either not affect TCP or, more likely, would increase it without increasing OAR toxicity because of the isotoxic design of PTP compared with the standard uniform dosing approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although the atlas has an impact on a significant number of patients, its applicability is limited to 40% to 50% of the patients receiving chemotherapy and radiation therapy by excluding patients whose tumor grows or shrinks very little. Studies using clinical data and radiomics (1719) have demonstrated that quantitative image features extracted from pretreatment scans can be used to predict tumor response (eg, volume shrinkage) to chemotherapy and radiation therapy, thereby identifying patients who may not benefit from PTP in advance of radiation therapy. However, even if the stratification of patients to PTP is wrong, the simultaneous integrated boost to the target predicted by PTP becomes a randomly located hot spot within the initial PTV, which would either not affect TCP or, more likely, would increase it without increasing OAR toxicity because of the isotoxic design of PTP compared with the standard uniform dosing approach.…”
Section: Discussionmentioning
confidence: 99%
“…The study of radiomics promises to improve patient‐specific care in radiation oncology by using the vast amounts of imaging data, acquired during radiation therapy (RT) . A method that has recently generated considerable interest is the extraction and analysis of texture features and their change over treatment (i.e., delta‐radiomics), as a means to quantitatively evaluate treatment response during RT delivery . Features may be designed in order to assess the amount of heterogeneity over a region of interest (ROI), or to quantify spatial information.…”
Section: Introductionmentioning
confidence: 99%
“…In patients undergoing thoracic radiotherapy or chemoradiotherapy, decreases in overall tumor activity (not SUV max ) 2 to 3 weeks into treatment correlated with overall survival and/or progression free survival. [46][47][48] Series examining PET-CT changes 4 to 5 weeks into chemoradiotherapy treatment also appeared to stratify responders and nonresponders, [49][50][51][52] but only one study showed an association of PET-CT changes with survival, 50 and these studies differed significantly in their benchmarks to evaluate PET-CT response. Table 4 summarizes these results.…”
Section: Identifying Those At Significant Risk Of Locoregional Failurementioning
confidence: 99%